2022
DOI: 10.1371/journal.pone.0262594
|View full text |Cite
|
Sign up to set email alerts
|

The impact of free vaccination policies under the Korean Influenza National Immunization Program: Trends in influenza vaccination rates in South Korea from 2010 to 2019

Abstract: Background Annual vaccination for influenza is recommended for high-risk populations for its high morbidity and mortality. South Korea provides free influenza vaccination to some target groups under the National Immunization Program (NIP), and discrepantly high vaccination rates are observed in such populations. In this study, we analyzed the trends in influenza vaccination rates and evaluated the impact of the recent expansion of financial coverage to children ≤12 years and pregnant women. Methods We conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Previous studies have consistently demonstrated similar results (34-36). The results from a recent study conducted in Korea also showed that a lower education level was associated with higher influenza vaccination coverage (37). It might be that people with low education levels have the need for preventive management because they have more possibility to work in fields that require more physical activities and less social support.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have consistently demonstrated similar results (34-36). The results from a recent study conducted in Korea also showed that a lower education level was associated with higher influenza vaccination coverage (37). It might be that people with low education levels have the need for preventive management because they have more possibility to work in fields that require more physical activities and less social support.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancy in vaccination coverages among target groups was also present: relatively low coverages were observed in pregnant women and people with chronic diseases. Previous studies showed that financial support is one of the most powerful factors which enhance influenza vaccination coverages [ 6 , 12 , 20 , 21 ]. As shown in Fig 1 , vaccination coverages of children ≤12 increased steeply after 2017–2018 along with the start of free vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Four subgroups were selected as target groups in our previous studies: adults aged ≥65, children aged ≤12, pregnant women, and people aged 19–64 with chronic diseases [ 6 , 12 ]. In the present study, considering the policy changes in 2020, we added two target subgroups: adults aged 62–64 and children aged 13–18.…”
Section: Methodsmentioning
confidence: 99%
“…For example, vaccination for children under 12 years old was gradually extended from 2016 to 2018, and the coverage rate increased dramatically from 61.2% in 2014 to 83.1% in 2019. In addition, when free vaccination was made available to pregnant women in 2019, the vaccination rate increased from 36.5% in 2014 to 68.5% in 2019 [57]. The effect of the free vaccination policy is not limited to South Korea.…”
Section: Discussionmentioning
confidence: 99%